Preparation of Pentafluorinated Phenyl-Monohydro[60]fullerenes - Shang, Wenli; Zhang, Jianmin; Chen, Xiaolei; Zou, Yuanhai; He, Shanshan; Zhao, Jingwei; Zhu, Shizheng (Synthesis, 2012)
Pentafluorinated phenyl-monohydro[60]fullerenes [C60(Arf)5H] are synthesized in good yields via reaction of the corresponding fluorinated phenyl copper reagent, itself prepared in situ from the fluorinated phenyl Grignard reagent (ArfMgBr) and copper(I) bromide–dimethyl sulfide complex, with [60]fullerene (C60) in 1,2-dichlorobenzene under a nitrogen atmosphere.
Keywords: fullerene; fluorinated phenyl; copper reagent; regioselective; five-fold addition